Application of longitudinal conductance in the estimation of the natural vulnerability of the guarani aquifer system in the São Paulo state - Braga, Antonio Celso De Oliveira [UNESP]; Francisco, Richard Fonseca [UNESP]; Birelli, Carlos Alberto; Blanco, Régis Gonçalves (UNESP - Universidade Estadual Paulista, 2018)
This paper presents the results obtained from geophysical data processing, which were acquired through vertical electrical soundings developed on occurrence area of the Guarani Aquifer System (GAS), in São Paulo state, Brazil. The Institute Technological Research (IPT) carried out these geoelectric data in the 1970s and 1980s. This work aimed to assess the natural vulnerability of the Guarani Aquifer System in São Paulo state. The geophysical surveys coupled to wells data produced consistent results, in terms of characterization of the regional geology and delineation of structural outline. According to the natural vulnerability map, the most vulnerable regions are located in the unconfined GAS. This result is compatible with those reported in previous studies, based on the use of other assessment models. Less vulnerable regions are concentrated in the central portion of the sedimentary basin (confinement GAS). Therefore, the use of longitudinal unit conductance produced robust results, representing a very promising parameter for estimating the natural vulnerability of aquifers. Thus, its application is feasible as an alternative to the traditional models, especially in regions with scarcity data, constituting an important tool for the protection of aquifers.
Aplicação da condutância longitudinal na estimativa da vulnerabilidade natural do sistema aquífero guarani no estado de São Paulo
Keywords: Geophysics; Guarani Aquifer System; Longitudinal Unit Conductance; Vulnerability